International Society of Urological Pathology (ISUP) Consensus Conference on Current Issues in Bladder Cancer. Working Group 2: Grading of Mixed Grade, Invasive Urothelial Carcinoma Including Histologic Subtypes and Divergent Differentiations, and Non-Urothelial Carcinomas. - Kamat, Ashish; Cheng, Liang; Adeniran, Adebowale; Al-Ahimadie, Hikmat; Algaba, Fernando; Bhattarai, Yves Allory Selina; Black, Peter; Berman, David; Bertz, Simone; Bubendorf, Lukas; Carlsen, Birgitte; Carvalho, Rita; et al. (American Journal of Surgical Pathology, 2024)
The 2022 International Society of Urological Pathology (ISUP) Consensus Conference on Urinary Bladder Cancer Working Group 2 was tasked to provide evidence-based proposals on the applications of grading in noninvasive urothelial carcinoma with mixed grades, invasive urothelial carcinoma including subtypes (variants) and divergent differentiations, and in pure non-urothelial carcinomas. Studies suggested that predominantly low-grade noninvasive papillary urothelial carcinoma with focal high-grade component has intermediate outcome between low- and high-grade tumors. However, no consensus was reached on how to define a focal high-grade component. By 2004 WHO grading, the vast majority of lamina propria-invasive (T1) urothelial carcinomas are high-grade, and the rare invasive low-grade tumors show only limited superficial invasion. While by 1973 WHO grading, the vast majority of T1 urothelial carcinomas are G2 and G3 and show significant differences in outcome based on tumor grade. No consensus was reached if T1 tumors should be graded either by the 2004 WHO system or by the 1973 WHO system. Because of the concern for underdiagnosis and underreporting with potential undertreatment, participants unanimously recommended that the presence of urothelial carcinoma subtypes and divergent differentiations should be reported. There was consensus that the extent of these subtypes and divergent differentiations should also be documented in biopsy, transurethral resection, and cystectomy specimens. Any distinct subtype and divergent differentiation should be diagnosed without a threshold cutoff, and each type should be enumerated in tumors with combined morphologies. The participants agreed that all subtypes and divergent differentiations should be considered high-grade according to the 2004 WHO grading system. However, participants strongly acknowledged that subtypes and divergent differentiations should not be considered as a homogenous group in terms of behavior. Thus, future studies should focus on individual subtypes and divergent differentiations rather than lumping these different entities into a single clinicopathological group. Likewise, clinical recommendations should pay attention to the potential heterogeneity of subtypes and divergent differentiations in terms of behavior and response to therapy. There was consensus that invasive pure squamous cell carcinoma and pure adenocarcinoma of the bladder should be graded according to the degree of differentiation. In conclusion, this summary of the International Society of Urological Pathology Working Group 2 proceedings addresses some of the issues on grading beyond its traditional application, including for papillary urothelial carcinomas with mixed grades and with invasive components. Reporting of subtypes and divergent differentiation is also addressed in detail, acknowledging their role in risk stratification. This report could serve as a guide for best practices and may advise future research and proposals on the prognostication of these tumors.
EVALuna2:570325